El apoyo de internet en la construcción de protocolos y en la generación de debates sobre temáticas particulares: “Un intento de unión del paradigma universal de cultura universitaria y la pluralidad de los paradigmas de racionalidad” (2021)
The present document is product on the attempt to share in the university plane a pedagogical experience. More than his innovation or universalist relevance in the educative plane, it tries to contribute to the formation challenge that brings with himself the implantation decree 808 of 2002. It responds to the idea, already raised by some authors, who exist in the university scope two paradigms in education: the modern and universalist model and, the new paradigm of the plurality of senses constructed by location contexts. In this sense, the writing recognizes kindness of both models and, bet by a dialectic game through as the student and the educator moves in both paradigms - they separate in some occasions and in others they play the same roll- within an active process of construction of knowledge. The excellent and facilitador resource of all this process is the use of the Network and, which is implicit in all this virtual activity, it is the necessity that the student expresses and develops his potential competitions, that between in a dialogistic process that obligatorily does not imply the physical space of the classroom.